2014
DOI: 10.1155/2014/709159
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Cardiac Autonomic Regulation in Mice Lacking ASIC3

Abstract: Integration of sympathetic and parasympathetic outflow is essential in maintaining normal cardiac autonomic function. Recent studies demonstrate that acid-sensing ion channel 3 (ASIC3) is a sensitive acid sensor for cardiac ischemia and prolonged mild acidification can open ASIC3 and evoke a sustained inward current that fires action potentials in cardiac sensory neurons. However, the physiological role of ASIC3 in cardiac autonomic regulation is not known. In this study, we elucidate the role of ASIC3 in card… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 49 publications
1
7
0
Order By: Relevance
“…Baseline BP in WT rats and KO rats: Regarding cardiovascular responses to activation of muscle afferents’ P2X3, it is interesting to observe a decreased baseline of BP and HR in ASIC3 KO rats. This is partly consistent with the previous study from Cheng et al, 34 in which the ASIC3 −/− mice demonstrated a blunt BP response under stress condition and the ratio of the low frequency power spectral density was lower in ASIC3 −/− mice than the ASIC3 +/+ mice. This indicates a blunted effect on the sympathetic control of cardiovascular activity following the global abolishing of the ASIC3.…”
Section: Discussionsupporting
confidence: 93%
“…Baseline BP in WT rats and KO rats: Regarding cardiovascular responses to activation of muscle afferents’ P2X3, it is interesting to observe a decreased baseline of BP and HR in ASIC3 KO rats. This is partly consistent with the previous study from Cheng et al, 34 in which the ASIC3 −/− mice demonstrated a blunt BP response under stress condition and the ratio of the low frequency power spectral density was lower in ASIC3 −/− mice than the ASIC3 +/+ mice. This indicates a blunted effect on the sympathetic control of cardiovascular activity following the global abolishing of the ASIC3.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, there is evidence that ASIC3 is also involved in control of blood pressure, as well as regulating breathing rate. For example, ASIC3 −/- mice have a lower systolic and diastolic blood pressure, coupled with a slightly, but not statistically significant, higher heart rate, as a potential compensatory role, compared to WT mice [ 104 ]. The link between ASIC3 and blood pressure regulation is further supported by the human genetic polymorphism rs2288646-A found in Taiwanese individuals, which is associated with a higher frequency of higher systolic and diastolic blood pressure, allele frequency being 9.7% amongst those with hypertension [ 105 ]; however, the effect of this polymorphism on channel function or expression is yet to be determined.…”
Section: Asic3 Expression and Its Pathophysiological Rolesmentioning
confidence: 99%
“…In support of this notion, Cheng et al (24) showed that ASIC3-null mice present normal baseline heart rate under basal conditions but abnormal autonomic regulation of cardiac activity in response to isoproterenol-induced myocardial ischemia. In addition, ASIC3-null mice have significative lower systolic and diastolic arterial blood pressure under stress than wild-type littermates (24). In support of the notion that ASIC3 plays a protective role in cardiac ischemia, histological studies revealed that Asic3 KO mice exhibit more severe left ventricular fibrosis and monocyte infiltration 7 days after isoproterenol-induced myocardial ischemia than wildtype littermates (23).…”
Section: Myocardial Ischemiamentioning
confidence: 92%
“…Activation of cardiac sensory neurons triggers sympathetic activation during cardiovascular disease states (90,97), which was proposed to elicit multifarious cardioprotective signals to limit the severity of the injury (11). In support of this notion, Cheng et al (24) showed that ASIC3-null mice present normal baseline heart rate under basal conditions but abnormal autonomic regulation of cardiac activity in response to isoproterenol-induced myocardial ischemia. In addition, ASIC3-null mice have significative lower systolic and diastolic arterial blood pressure under stress than wild-type littermates (24).…”
Section: Myocardial Ischemiamentioning
confidence: 98%